Effect of dried Gliricidia sepium leaf supplement on feed intake, digestibility and nitrogen retention in sheep fed dried KW4 elephant grass (Pennisetum purpureum) ad libitum - Mpairwe, D.R.; Sabiiti, E.N.; Mugerwa, J.S. (Springer, 1998)
A feeding experiment was conducted to study the effects of supplementation with dried Gliricidia sepium leaves on dry matter (DM) intake, digestibility and nitrogen retention in sheep fed KW4 elephant grass. Four mature rams were fed elephant grass ad libitium supplemented with four levels of gliricidia leaves (0, 4, 8 and 12 gDM kg-1wt day -1) in a 4x4 Latin swuare design. Supplementation with gliricidia leaves decreased elephant grass DM intake (g DM day-1 or g DM kg-1 BW 0.75 day -1). However, the effect of supplementation of total DM intake of the rations was not significant (P>0.05). Total crude protein intake significantly (P<0.001) increased with increasing levels of gliricidia supplementation. Total DM digestibility and body weight changes were significantly (P<0.05) improved by gliricidia supplementation; with the highest digestibility coefficient (60.5) improved by gliricidia supplementation; with the highest digestibility coefficient (60.5 percent) and body weight gain (89.3 g/day) obtained at 8 g DM kg -1wt day -1. Gliricidia supplementation significantly (P<0.001) improved nitrogen intake, absorbed nitrogen and retained nitrogen but with no significant difference at 8 and 12 g DM kg -1wt day -1 level of supplementation. The highest efficiency of N retention by sheep (44.9 percent) was obtained at 8 g DM kg -1wt day -1 level of gliricidia supplementation. The results indicated that supplemention of KW4 elephant grass with small quantities of gliricidia leaves up to 8 g DM kg -1wt day -1 enhance utilisation efficiency of the total ration. Further increases in the level of gliricidia supplementation, under the conditions of this experiment, reduced the intake of elephant grass leading to substitution effects of the basal.